The Legal Framework of Media Ownership in Bulgaria – Specifics and Development - Veleva, Simona (Research Papers, 2020)
The current study suggests a brief comparative review of the legal framework of media ownership in Europe, as well as an analysis of the development of the Bulgarian legislation, especially in the light of the newly amended law on Compulsory Deposit of Printed and Other Works and the Disclosure of Distributors and Media Service Providers. The analysis concludes that the current legislation is development in a positive direction, but public relations related to transparency and informing the society regarding the media ownership in Bulgaria require a better systematized and unified arrangement and coordination between the competent authorities, proportionate sanctions based on the principles of the Constitution and guaranteeing freedom of speech as a value. To achieve these conclusions, the comparative, the systematic and the structural-functional methods are used.
Keywords: Media; Media ownership in Bulgaria; Ownership; Media concentration